Pengaruh Likuiditas, Leverage, Dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Sektor Manufaktur Subsektor Semen Di Bursa Efek Indonesia Periode 2016-2020 - Kiki Floresti Zujeny; Ima Andriyani; Mariyam Zanariah; Lusia Nargis (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of liquidity, leverage, and profitability on firm value in the cement sub-sector companies on the Indonesia Stock Exchange. The type of research used is descriptive quantitative. The population in this study is the cement sub-sector manufacturing sector companies on the IDX for the 2016-2020 period. The sampling method in this research is non-probability sampling using saturated sampling technique. Simultaneous hypothesis test results show that the variables of liquidity, leverage and profitability affect Price to Book Value (PBV). This shows the value of sig F (0.001) <0.05. The results of the partial test also show that the Liquidity variable (CR) does not affect Price to Book Value (PBV) indicated by the value of sig t (0.651) > a (0.05), the Leverage variable (DER) affects Price to Book Value (PBV) indicated with the value of sig t (0.013) < a (0.05). And the Profitability (ROA) variable affects Price to Book Value (PBV) indicated by the value of sig t (0.006) < a (0.05).